ANALISIS KELAYAKAN EKONOMI PADA PEMBANGUNAN PERKANTORAN TOWER POROS MARITIM SURABAYA - Eka Nurus Sakinah; I Nyoman Dita Pahang Putra; Anna Rumintang (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
The increasing population and business development in Surabaya have made large companies need space for their employees. Assessing the characteristic of a development project must conduct a feasibility study. One of the feasibility studies conducted is to conduct an economic feasibility analysis. This analysis is carried out to ensure that the project is feasible from an economic aspect. The purpose of this study is to determine how much the benefits and costs are obtained and the extent of its economic feasibility. The project that will be examined in this final project is the Surabaya Maritime Tower Poros office. Then the feasibility of this office development project is based on the calculation of the Benefit-Cost Ratio (BCR), Net Present Value (NPV), Internal Rate of Return (IRR), and Return on Investment (ROI). The results of this economic feasibility analysis obtained a positive NPV value of IDR.32,995,643,307.00, IRR value of 12.08%, ROI of 15.76% and BCR 3.2. Then the return on investment is calculated using an annual cash flow with a variable amount of 2 years 10 months and 8 days.